The Text of the Ascension Narratives (Luke 24.50–3; Acts 1.1–2, 9–11) - Zwiep, Arie W. (New Testament studies, 1996)
It is by no means an exaggeration to claim that the tendency of modern textual critics and exegetes is to regard the long disputed text-critical issue of Luke's final pericope (Luke 24.50–3) as more or less settled in favour of the authenticity of the so-called ‘longer (non-Western) text’ (i.e. containing the phrases κα⋯ ⋯νεφέρετο εἰς τ⋯ν ούρανόν, v. 51 and προσκυνήσαντες αύτόν, v. 52). Typical of the scholarly consensus is the almost unanimous adoption of the disputed words by modern Greek text editions, translations and exegetical studies, a trend which is not least inspired by the fact that the disputed words are attested in the oldest surviving copy of the Gospel of Luke, Papyrus 75 ($$$ = Papyrus Bodmer XIV), an early third-century MS closely affiliated with Codex Vaticanus (B). In the opening chapter of Acts the Textual situation is not essentially different. Despite continuing scholarly debate concerning the antiquity and origin of the Western text tradition (infra), in general, contemporary scholarship supports the ‘Alexandrian’ text.